Zeit in Gesetzen erfasst - G. W. F. Hegels Theorie der Kodifikation. - Müller, Michael W. (Recht und Philosophie, 2021)
The thesis analyzes Georg Wilhelm Friedrich Hegel's contribution to the German codification debate in the 19th century and its potential for a modern theory of codification. According to Hegel, codification means abstraction and system formation based on the actual, with respect to the reasonable law. On this basis, codification is a constant process and as much a requirement of a civilized society of free citizens as it is a contribution to its realization.